Ion Induced Changes in the Structure of Bordered Pit Membranes - Lee, Jinkee; Holbrook, Noel Michele; Zwieniecki, Maciej A. (Frontiers in Plant Science, 2012)
Xylem hydraulic resistance varies with ion concentration in sap solution. It is assumed that this variation in resistance results from hydrogel like properties of pectins located in bordered pit membranes separating adjacent vessels. Although kinetics of the resistance change suggests swelling/deswelling behavior of the pectins, there is no direct evidence of this activity. In this report we provide evidence of structural changes in bordered pit membranes responding to variation in ionic concentration of solute around it using atomic force microscopy (AFM). AFM revealed bordered pit membranes as relatively smooth, soft and lacking any sharp edges surface when submerged in de-ionized water, in contrast to pictures from scanning electron microscope (SEM) or AFM performed on air dry material. Exposure of the bordered pit membranes to 50 mM KCl solution resulted in significant changes in both surface physical properties with and elevation features as bordered pit membrane became harder, with visible edges of fibers and collapsed, while no change in porosity was observed. Analysis suggests a need for a major shift in our understanding to the physical bases of variable xylem resistance from change in porosity to change in pathway length. Findings support the role of actuating properties of hybrid hydrogel-cellulose materials in water redistribution and embolism resistance.